Guidelines for process safety acquisition evaluation and post merger integration. (Wiley, 2010)
It is crucial for process safety professionals to be aware of best practices for post merger integration at any level. A compilation of industry best practices from both technical and financial perspectives, this book provides a single reference that addresses acquisitions and merger integration issues related to process safety. Presently, there are limited references on how to handle acquisitions in several different CCPS publications and almost no coverage of the post-merger integration issue, so this reference fills a notable gap in the coverage.
Keywords: Chemical industry -- Management.; Chemical industry -- Safety regulations.; elektronické knihy; electronic books